Question
Fri March 12, 2010 By: Kirti Chawla

plzz answer ........

Expert Reply
Sat March 13, 2010

2x + 3y -7 =0        ... (1)

(m-1)x - (m+y) = (3m-1)

(m-1)x - y = 3m-1+m

(m-1)x - y = 4m-1 .... (2)

We can write equation (1),

as 2x + 3y = 7

-2x/3 - y = -7/3

Comparing with (2), coefficients of y i.e. -1 in both equations, and if other coefficients are also same, then the given pair of equations will have inifinitely many solutions.

Hence, m-1 = -2/3,

m = 1/3 or

4m - 1 = -7/3

m = -1/3.

Regards,

Team,

TopperLearning.

 

 

Home Work Help